Use of pesticides and risks to human health: overview of the rural area of the municipality of Independência - RS (Research, Society and Development, 2021)
The general objective of the study was to describe health disorders and aspects related to the use of pesticides by rural workers in the municipality of Independência-RS. To this end, a quantitative research of the exploratory descriptive type was developed, which was carried out in the municipality of Independência - Rio Grande do Sul, in a sample of 63 farmers. Data were collected through a form with objective questions, from November 2019 to February 2020. The analysis of the results was based on descriptive statistical analysis. Farmers are aware of the risks associated with the use of pesticides, and have already presented health disorders associated with exposure to such products, such as nausea, diarrhea, skin irritation, burning eyes, but they have not had a diagnosis of intoxication. The risk factors associated with the occurrence of health disorders due to exposure to pesticides in the municipality of Independência-RS are low education, the inadequate use of personal protective equipment, use of active ingredients with varying degrees of toxicity, including some classified as carcinogens, and the lack of adequate storage for pesticides. Researches such as these can help to promote the health of rural workers, thus preventing the number of poisonings and harm to human health.